Streamlining Food Management for Legal and Safe Small Industries - Marlita, Marlita; Abidin, Zaenal; Wandi, Wandi; Wulandari, Triyana (Zabags International Journal of Engagement, 2024)
This research aims to improve safe and legal food management in small industries by providing assistance through training and the provision of simple tools. The method used is a qualitative approach with case studies, involving in-depth interviews, observations, and document analysis regarding food safety regulations. Data is collected from small businesses in the food sector to identify the challenges they face in implementing food safety standards. The results of the study show that many business actors do not fully understand the applicable regulations, and access to adequate training and resources is very limited. However, after the implementation of the assistance program, there has been a significant improvement in food safety understanding and practices, as well as a reduction in errors in data recording. The recommendations of this study include the need for government support in providing affordable training and access to resources, as well as the development of online platforms to facilitate business actors in food safety management. With these measures, it is hoped that small industries can adapt to changes in the market and regulations, thereby improving product quality and competitiveness in the local market